Augustine and academic skepticism : a philosophical study - Dutton, Blake D., 1962- (Cornell University Press, 2016)
Among the most important, but frequently neglected, figures in the history of debates over skepticism is Augustine of Hippo (354-430 CE). His early dialogue, Against the Academics, together with substantial material from his other writings, constitutes a sustained attempt to respond to the tradition of skepticism with which he was familiar. This was the tradition of Academic skepticism, which had its home in Plato's Academy and was transmitted to the Roman world through the writings of Cicero (106-43 BCE). Augustine and Academic Skepticism is the first comprehensive treatment of Augustine's critique of Academic skepticism. In clear and accessible prose, Blake D. Dutton presents that critique as a serious work of philosophy and engages with it precisely as such. While Dutton provides an extensive review of Academic skepticism and Augustine's encounter with it, his primary concern is to articulate and evaluate Augustine's strategy to discredit Academic skepticism as a philosophical practice and vindicate the possibility of knowledge against the Academic denial of that possibility. In doing so, he sheds considerable light on Augustine's views on philosophical inquiry and the acquisition of knowledge. -- from dust jacket.